EFL Students’ Perception of Using Grammarly in Undergraduate Paper Writing - Raihan; R. Bunga Febriani; Leni Irianti (Universitas Bengkulu, 2023)
This research discusses about EFL Students’ Perception of Using Grammarly in Undergraduate Paper Writing. The objective of this study was aimed to elaborate the challenges faced by students’ in writing a research paper by using Grammarly and investigated the students’ perception of using Grammarly in undergraduate paper writing. This study used descriptive qualitative method, involved 23 students’ of English Education who used Grammarly in writing a paper. Brief rating scales questionnaires were used to gather the data. The results showed that students’ responded positively to the use of Grammarly in undergraduate paper writing. Most of the students agreed that using Grammarly makes the process of writing more clearly, easy, and fascinating. Grammarly can help students’ in correcting the grammatical errors and plagiarism in their writing. However, writing a paper should be with the correct and good grammar so that the reader can easily to found out the meaning and also more understandable the paper. The researcher suggested for the next research to focus on the teacher perception of using Grammarly to assist the students’ in writing a research paper.